Composite material containing heterostructure filler as well as preparation and application of composite material

By using solid-phase sintering method in electronic packaging materials to prepare negative thermal expansion fillers and coat them with thermally conductive fillers, forming heterostructure fillers and composited with polymer matrix, the thermal management difficulties of existing materials under high power and miniaturization conditions are solved. It achieves a combination of high thermal conductivity and low thermal expansion coefficient, and improves the reliability and processing performance of the material.

CN119410103AActive Publication Date: 2025-02-11HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411656788.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Existing electronic packaging materials have difficulty in thermal management under high power and miniaturization conditions, and while traditional high-performance composite materials reduce the thermal expansion coefficient, the mechanical properties and processing difficulties of materials increase and the cost increases.

Method used

The negative thermal expansion packing is prepared by solid phase sintering method, and the thermally conductive filler is coated on its surface to form a heterostructure filler and a polymer matrix to obtain a composite material with high thermal conductivity and low thermal expansion coefficient.

Benefits of technology

The high thermal conductivity and low thermal expansion coefficient of the composite material are achieved at low filling amounts, reducing the interface thermal resistance, improving the thermal conductivity, enhancing the dimensional stability in the thermal cycle, and ensuring the reliability of the electronic packaging system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410103A_ABST
    Figure CN119410103A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material containing a heterostructure filler as well as preparation and application of the composite material. The composite filler comprises 65-95 parts by volume of a polymer matrix and 5-35 parts by volume of the heterostructure filler, wherein the heterostructure filler comprises a negative thermal expansion filler and a heat conduction filler, and the heat conduction filler coats the outer layer of the negative thermal expansion filler. According to the composite material, the heterostructure filler with the negative thermal expansion coefficient is selected to be compounded with the polymer matrix, the thermal expansion coefficient of the composite material is reduced to a proper range under the condition of low filling amount, and the problem of high processing viscosity caused by high filling amount in the using process of the positive thermal expansion filler is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic packaging materials, and in particular relates to a composite material containing a heterogeneous structure filler and a preparation method and application thereof. Background Art

[0002] With the advent of the 5G era, electronic components are developing towards high integration, high power and miniaturization. The problem of heat accumulation in their narrow internal space is becoming more and more serious, affecting their service life and operational reliability. It is very important to effectively manage the thermal performance of electronic packaging materials. In addition, electronic packaging materials should have a suitable thermal expansion coefficient to ensure that the thermal stress of solder joints under high and low temperature cycles can be effectively dispersed to prevent solder joint cracking. Polymer materials are highly favored in electronic packaging materials due to their advantages such as insulation resistance, corrosion resistance, light weight and good processability, but their low intrinsic thermal conductivity and high thermal expansion coefficient limit their application scenarios.

[0003] The preparation of traditional high-performance composite materials is mainly based on simple filling with high thermal conductivity inorganic fillers, such as aluminum oxide, boron nitride, silicon carbide and carbon nanotubes. These high thermal conductivity inorganic fillers have positive thermal expansion characteristics. Positive thermal expansion inorganic fillers usually require a high filling amount (>50vol%) to reduce the thermal expansion coefficient of the composite system to a reasonable range. However, a large amount of filling inorganic fillers will inevitably lead to the deterioration of the mechanical properties of the material and the increase of processing difficulty and cost, which greatly limits the further application of composite materials. The design and preparation of high-performance polymer-based composite materials with both low thermal expansion coefficient and high thermal conductivity are faced with challenges. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a composite material containing a heterogeneous structure filler and a preparation method and application thereof. The method first uses a solid phase sintering method to prepare a negative thermal expansion filler, then coats a thermal conductive filler on the surface of the negative thermal expansion filler to obtain a heterogeneous structure filler, and finally composites it with a polymer matrix to obtain the composite material, which can be used as an electronic packaging material. In addition, the heterogeneous structure filler has the characteristics of both high thermal conductivity and low thermal expansion coefficient, and can obtain a composite material with both high thermal conductivity and low thermal expansion coefficient at a low filling amount.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A composite material containing a heterogeneous structure filler, characterized in that it comprises 65 to 95 parts by volume of a polymer matrix and 5 to 35 parts by volume of a heterogeneous structure filler;

[0007] Wherein, the heterogeneous structure filler includes a negative thermal expansion filler and a thermal conductive filler, and the thermal conductive filler is coated on the outer layer of the negative thermal expansion filler.

[0008] According to an embodiment of the present invention, the polymer matrix is ​​at least one of epoxy resin, polyimide, phenolic resin, polyphenylene ether and polydimethylsiloxane.

[0009] According to an embodiment of the present invention, the volume fraction of the polymer matrix is ​​65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts.

[0010] According to an embodiment of the present invention, the negative thermal expansion filler is zinc pyrophosphate, denoted as Zn 2-x M x P 2 O 7 , wherein M is selected from any one of Cu, Mg, Ca, Mn, Fe, Co, Ni, Ba, and Sr, and 0<x<2, for example, x is 0.1, 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8 or 1.9.

[0011] According to an embodiment of the present invention, the negative thermal expansion filler is a random particle. Preferably, the average particle size of the negative thermal expansion filler is 0.1 to 30 μm.

[0012] According to an embodiment of the present invention, the thermal conductivity of the thermally conductive filler is 60-70 W / m·K.

[0013] According to an embodiment of the present invention, the thermal conductive filler is zinc oxide, and its morphology is one or more of spherical, flake, columnar or needle-shaped. Preferably, the average diameter of the spherical zinc oxide is 0.1-0.5 μm, the average lateral size of the flake zinc oxide is 0.1-0.8 μm, the diameter-to-thickness ratio is (5-50):1, and the length of the columnar zinc oxide and the needle-shaped zinc oxide are both 1-5 μm, and the aspect ratio is (2-10):1.

[0014] Preferably, the thermal conductivity of the zinc oxide is 60-70 W / m·K.

[0015] According to an embodiment of the present invention, the volume fraction of the heterogeneous structure filler is 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or 35 parts.

[0016] The present invention also provides a method for preparing the composite material containing the heterogeneous structure filler, characterized in that the method comprises the following steps:

[0017] (S1) preparing or preparing a negative thermal expansion filler;

[0018] (S2) coating the outer layer of the negative thermal expansion filler with a thermally conductive filler to obtain a heterogeneous structure filler;

[0019] (S3) Mixing and curing the heterogeneous structure filler, polymer matrix and curing agent to obtain the composite material.

[0020] According to an embodiment of the present invention, in step (S1), the preparation method of the negative thermal expansion filler is as follows:

[0021] (1) Raw material mixing: mixing an oxide containing an M element, zinc oxide and a phosphorus oxyacid compound, and grinding the obtained mixed powder to obtain a zinc pyrophosphate precursor;

[0022] The M is selected from any one of Cu, Mg, Ca, Mn, Fe, Co, Ni, Ba, and Sr;

[0023] (2) Precursor calcination: calcining the zinc pyrophosphate precursor obtained in step (1), grinding the calcined product to obtain a negative thermal expansion filler.

[0024] According to an embodiment of the present invention, in step (S2), the method for preparing the heterogeneous structure filler is specifically:

[0025] (3) Seed formation: Dissolve the soluble zinc salt in an alcohol solvent of sodium hydroxide, then add the negative thermal expansion filler of step (2) and mix to obtain zinc pyrophosphate supported by zinc oxide seeds, denoted as Zn 2-x M x P 2 O 7 @ZnO-dot;

[0026] (4) Crystal growth: Zinc nitrate hexahydrate, hexamethylenetetramine and the Zn obtained in step (3) are added to the mixture. 2-x M x P 2 O 7 @ZnO-dot is heated and mixed in water to obtain the heterogeneous structure filler.

[0027] According to an embodiment of the present invention, in step (1), the phosphorus oxyacid compound is one or more of diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, metaphosphoric acid, and pyrophosphoric acid.

[0028] According to an embodiment of the present invention, in step (1), the oxide containing the M element is selected from one of copper oxide, magnesium oxide, calcium oxide, manganese oxide, ferrous oxide, cobalt oxide, nickel oxide, barium oxide or strontium oxide.

[0029] Preferably, the added amounts of the oxide containing the M element, zinc oxide and phosphorus oxyacid compound are added according to the molar ratio of the M element, zinc element and phosphorus element in the zinc pyrophosphate precursor of x:(2-x):2, wherein 0<x<2.

[0030] According to an embodiment of the present invention, in step (2), the calcination atmosphere is air.

[0031] According to an embodiment of the present invention, in step (2), the calcination specifically comprises: firstly performing a pre-calcination, cooling the pre-calcined product, and then performing a secondary calcination;

[0032] The pre-calcination temperature is 600-800°C, and the pre-calcination time is 1-4h;

[0033] The secondary calcination temperature is 800-1000°C, and the secondary calcination time is 1-4h.

[0034] According to an embodiment of the present invention, the pre-calcined product is cooled to below the pre-calcination temperature, for example, to room temperature.

[0035] According to an embodiment of the present invention, in step (1) or step (2), the grinding is one of ball milling and sand milling.

[0036] According to an embodiment of the present invention, in step (1) or step (2), grinding media may be added during the grinding process. For example, the grinding media is agate grinding balls.

[0037] According to an embodiment of the present invention, in step (1), a grinding aid may be added during the grinding process, and the grinding aid is at least one of ethanol, isopropanol, acetone and water.

[0038] According to an embodiment of the present invention, in step (1), the mass ratio of the mixed powder, grinding media and grinding aid is 1:(5-10):(1-2).

[0039] According to an embodiment of the present invention, in step (2), the mass ratio of the calcined product, the grinding medium and the grinding aid is 1:(5-10):(1-2).

[0040] According to an embodiment of the present invention, step (1) further comprises drying the ground product to obtain a zinc pyrophosphate precursor.

[0041] According to an embodiment of the present invention, in step (2), the calcined product is ground after being cooled.

[0042] According to an embodiment of the present invention, in step (3), the soluble zinc salt is at least one of zinc acetate, zinc acetate dihydrate, zinc nitrate hexahydrate, zinc chloride, and zinc sulfate.

[0043] According to an embodiment of the present invention, in step (3), the alcohol solvent is at least one of methanol and ethanol. Preferably, the content of the alcohol solvent is not particularly limited, as long as it can dissolve the soluble zinc salt and sodium hydroxide.

[0044] According to an embodiment of the present invention, in step (3), the mass ratio of the soluble zinc salt to sodium hydroxide is (0.7-4):1.

[0045] According to an embodiment of the present invention, in step (3), the mass ratio of the negative thermal expansion filler to the soluble zinc salt is 1:(0.01-1).

[0046] According to an embodiment of the present invention, in step (4), the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is (0.5-5):1, and preferably, the concentration of zinc nitrate hexahydrate is 0.01-0.1 mol / L.

[0047] According to an embodiment of the present invention, in step (4), zinc nitrate hexahydrate and Zn 2-x M x P 2 O 7 @The mass ratio of ZnO-dot is 1:(0.2~4).

[0048] According to an embodiment of the present invention, in step (4), the heating temperature is 80 to 100° C., and the mixing time is 3 to 9 hours.

[0049] According to an embodiment of the present invention, step (4) further comprises post-processing the prepared product such as separation, washing, and drying. For example, the separation method is one of reduced pressure filtration, centrifugation, and gravity filtration; the drying method is one of vacuum drying and heating drying, and the drying temperature is 60 to 200°C.

[0050] According to an embodiment of the present invention, in step (S3), the curing agent is at least one of 2-methylimidazole, 2,4-dimethylimidazole, 2-ethylimidazole, 2-phenylimidazole, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, triethylenetetramine, and isophoronediamine.

[0051] According to an embodiment of the present invention, in step (S3), the curing conditions are pre-curing at 50-100° C. for 1-3 hours, and then curing at 120-180° C. for 3-8 hours.

[0052] According to an embodiment of the present invention, in step (S3), the mass ratio of the curing agent to the polymer matrix is ​​(1-96):100.

[0053] As an exemplary embodiment of the present invention, step (S3) comprises:

[0054] The composite material containing the heterogeneous structure filler is obtained by mixing, degassing and curing the heterogeneous structure filler, the polymer matrix and the curing agent.

[0055] The present invention also provides an application of the composite material containing heterogeneous structure fillers in electronic packaging materials or thermal interface materials.

[0056] Beneficial effects of the present invention:

[0057] 1. In the composite material containing heterogeneous structure fillers provided by the present invention, the thermally conductive filler is coated on the outer layer of the negative thermal expansion filler, so that the thermally conductive fillers on the surface of the negative thermal expansion filler contact with each other to form a continuous thermal conductive network, thereby reducing the interface thermal resistance of the composite material and improving the thermal conductivity.

[0058] 2. The present invention provides a composite material containing a heterogeneous structure filler, which selects a heterogeneous structure filler with a negative thermal expansion coefficient and is compounded with a polymer matrix. The thermal expansion coefficient of the composite material is reduced to an appropriate range at a lower filling amount, thereby avoiding the high processing viscosity problem caused by the high filling amount of the positive thermal expansion filler during use. At the same time, its dimensional stability in thermal cycles is improved to ensure the reliability of the electronic packaging system.

[0059] 3. The method for preparing a composite material containing a heterogeneous structure filler provided by the present invention has the characteristics of simple operation, mild conditions, easy control and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a scanning electron microscope photograph of zinc oxide-coated magnesium zinc pyrophosphate (i.e., heterogeneous structure filler) in Example 1.

[0061] Figure 2 This is a scanning electron microscope photo of magnesium zinc pyrophosphate in Comparative Example 2.

[0062] Figure 3 1 is a graph showing the thermal conductivity performance of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1.

[0063] Figure 4 It is a thermal expansion performance diagram of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1. DETAILED DESCRIPTION

[0064] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0065] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0066] Embodiment 1:

[0067] A composite material containing a heterogeneous structure filler comprises 70 parts by volume of epoxy resin and 30 parts by volume of zinc oxide-coated magnesium zinc pyrophosphate heterogeneous structure filler.

[0068] The preparation of the heterogeneous structure filler comprises the following steps:

[0069] (1) Raw material mixing: Magnesium oxide, zinc oxide and ammonium dihydrogen phosphate were mixed at a molar ratio of 0.4:1.6:2 to obtain a powder. The powder, agate grinding balls and ethanol were then mixed evenly at a mass ratio of 1:7:2, and ball milled at a speed of 300 rpm for 3 h. Finally, the ball milled product was dried to obtain a zinc magnesium pyrophosphate precursor.

[0070] (2) Precursor calcination: The zinc magnesium pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 800° C. and a calcination time of 2 h, respectively; after the product is cooled to room temperature, it is secondary calcined at a calcination temperature of 900° C. and a calcination time of 2 h, respectively; after cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler zinc magnesium pyrophosphate powder having an average particle size of 2 μm.

[0071] (3) Seed formation: zinc acetate dihydrate and sodium hydroxide are dissolved in an ethanol solvent at a mass ratio of 3.4:1, and then the zinc magnesium pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc acetate dihydrate is 1:0.1), and the mixture is fully mixed. After separation, washing, and drying, zinc magnesium pyrophosphate supported by zinc oxide seeds is obtained, which is denoted as Zn 1.6 Mg 0.4 P 2 O 7 @ZnO-dot.

[0072] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine are dissolved in deionized water at a molar ratio of 1:1, wherein the concentration of zinc nitrate hexahydrate is 0.05 mol / L, and then the mixture of step (3) is added thereto. The obtained Zn 1.6 Mg 0.4 P 2 O 7 @ZnO- dot (Zinc nitrate hexahydrate and Zn 1.6 Mg 0.4 P 2 O 7 @ZnO-dot The mass ratio of zinc oxide to magnesium zinc pyrophosphate was 1:4, stirred at 95°C for 9h, then filtered under reduced pressure, washed, and dried by heating at 150°C to obtain a heterogeneous structure filler of zinc oxide coated with magnesium zinc pyrophosphate, wherein the zinc oxide morphology was flaky, with an average lateral size of 0.5μm and a diameter-to-thickness ratio of 5:1.

[0073] The preparation method of the composite material is: 70 parts of epoxy resin, 30 parts of heterogeneous structure filler, methyl hexahydrophthalic anhydride and 2,4-dimethylimidazole are mixed and cured to obtain the composite material, wherein the mass ratio of methyl hexahydrophthalic anhydride to epoxy resin is 95:100, and the mass ratio of 2,4-dimethylimidazole to epoxy resin is 1:100; the curing conditions are pre-curing at 100°C for 2 hours, and then curing at 150°C for 5 hours.

[0074] Embodiment 2:

[0075] A composite material containing a heterogeneous structure filler comprises 80 parts of polyimide and 20 parts of a heterogeneous structure filler of zinc oxide-coated zinc manganese pyrophosphate.

[0076] The preparation of the heterogeneous structure filler comprises the following steps:

[0077] (1) Raw material mixing: manganese oxide, zinc oxide and diammonium hydrogen phosphate were mixed at a molar ratio of 0.2:1.8:2 to obtain a powder. The powder, agate grinding balls and isopropanol were then mixed evenly at a mass ratio of 1:5:2, and sand-milled at a speed of 200 rpm for 2 h. Finally, the sand-milled product was dried to obtain a zinc manganese pyrophosphate precursor.

[0078] (2) Precursor calcination: The zinc manganese pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 600° C. and a calcination time of 2 h, respectively. After the product is cooled to room temperature, it is secondary calcined at a calcination temperature of 800° C. and a calcination time of 3 h, respectively. After cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler zinc manganese pyrophosphate powder having an average particle size of 30 μm.

[0079] (3) Seed formation: zinc acetate and sodium hydroxide are dissolved in a methanol solvent at a mass ratio of 4:1, and then the zinc manganese pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc acetate is 1:0.05), and the mixture is fully mixed. After separation, washing, and drying, zinc manganese pyrophosphate supported by zinc oxide seeds is obtained, which is recorded as Zn 1.8 Mn 0.2 P2O7@ZnO-dot.

[0080] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 5:1, wherein the concentration of zinc nitrate hexahydrate was 0.01 mol / L, and the Zn obtained in step (3) was added thereto. 1.8 Mn 0.2 P 2 O 7 @ZnO-dot( Zinc nitrate hexahydrate and Zn 1.8 Mn 0.2 P 2 O 7 @ZnO-dot mass ratio is 1:2), stirred at 80°C for 3h, then centrifuged, washed, and vacuum dried at 80°C to obtain a zinc oxide-coated zinc manganese pyrophosphate heterostructure filler, wherein the zinc oxide morphology is spherical and its average diameter is 0.1μm.

[0081] The composite material is prepared by mixing and curing 80 parts of polyimide, 20 parts of heterogeneous structure filler and 2,4-dimethylimidazole to obtain the composite material, wherein the mass ratio of 2,4-dimethylimidazole to polyimide is 6:100, and the curing conditions are pre-curing at 60°C for 2h and then curing at 150°C for 8h.

[0082] Embodiment 3:

[0083] A composite material containing a heterogeneous structure filler comprises 75 parts of phenolic resin and 25 parts of a heterogeneous structure filler of zinc oxide-coated zinc nickel pyrophosphate.

[0084] The preparation of the heterogeneous structure filler comprises the following steps:

[0085] (1) Raw material mixing: nickel oxide, zinc oxide and phosphoric acid were mixed at a molar ratio of 0.5:1.5:2 to obtain a powder. The powder, agate grinding balls and deionized water were then mixed evenly at a mass ratio of 1:10:1, and ball milled at a speed of 500 rpm for 4 hours. Finally, the ball milled product was dried to obtain a nickel zinc pyrophosphate precursor.

[0086] (2) Precursor calcination: The nickel zinc pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 700° C. and a calcination time of 1 h, respectively; after the product is cooled to room temperature, it is secondary calcined at a calcination temperature of 1000° C. and a calcination time of 2 h, respectively; after cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler nickel zinc pyrophosphate powder having an average particle size of 0.2 μm.

[0087] (3) Seed formation: Zinc nitrate hexahydrate and sodium hydroxide are dissolved in an ethanol solvent at a mass ratio of 0.7:1, and then the zinc nickel pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc nitrate hexahydrate is 1:1), and the mixture is fully mixed. After separation, washing, and drying, zinc nickel pyrophosphate supported by zinc oxide seeds is obtained, which is recorded as Zn 1.5 Ni 0.5 P 2 O 7 @ZnO-dot.

[0088] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 0.5:1, wherein the concentration of zinc nitrate hexahydrate was 0.1 mol / L, and the Zn obtained in step (3) was added thereto. 1.5 Ni 0.5P 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and Zn 1.5 Ni 0.5 P 2 O 7 @ZnO-dot has a mass ratio of 1:1), stirred at 100°C for 9 hours, and then gravity filtered, washed, and heated and dried at 200°C to obtain a zinc oxide-coated zinc nickel pyrophosphate heterostructure filler, wherein the zinc oxide morphology is columnar, with a length of 5 μm and an aspect ratio of 10:1.

[0089] The composite material is prepared by mixing and curing 75 parts of phenolic resin, 25 parts of heterogeneous structure filler and triethylenetetramine to obtain the composite material, wherein the mass ratio of triethylenetetramine to phenolic resin is 60:100, and the curing conditions are pre-curing at 50°C for 3 hours and then curing at 120°C for 5 hours.

[0090] Embodiment 4:

[0091] A composite material containing a heterogeneous structure filler comprises 90 parts of polyphenylene ether and 10 parts of a heterogeneous structure filler of zinc oxide-coated calcium zinc pyrophosphate.

[0092] The preparation of the heterogeneous structure filler comprises the following steps:

[0093] (1) Raw material mixing: Calcium oxide, zinc oxide and metaphosphoric acid are mixed in a molar ratio of 1:1:2 to obtain a powder. The powder, agate grinding balls and acetone are then mixed evenly in a mass ratio of 1:8:1, and sand-milled at a speed of 300 rpm for 4 hours. Finally, the sand-milled product is dried to obtain a zinc calcium pyrophosphate precursor.

[0094] (2) Precursor calcination: The calcium zinc pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 750° C. and a calcination time of 3 h, respectively; the product is cooled to room temperature and then subjected to secondary calcination at a calcination temperature of 800° C. and a calcination time of 1 h, respectively; after cooling, the calcined product is ground according to step (1) to obtain a negative thermal expansion filler calcium zinc pyrophosphate powder having an average particle size of 1 μm.

[0095] (3) Seed formation: zinc chloride and sodium hydroxide are dissolved in a methanol solvent at a mass ratio of 1:1, and then the calcium zinc pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc chloride is 1:0.5), and the mixture is fully mixed. After separation, washing, and drying, the calcium zinc pyrophosphate supported by zinc oxide seeds is obtained, which is recorded as ZnCaP 2 O 7 @ZnO-dot.

[0096] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 3:1, wherein the concentration of zinc nitrate hexahydrate was 0.09 mol / L, and the ZnCaP obtained in step (3) was added thereto. 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and ZnCaP 2 O 7 The mixture was stirred at 95°C for 4 hours, and then centrifuged, washed, and vacuum dried at 100°C to obtain a zinc oxide-coated calcium zinc pyrophosphate heterostructure filler, in which the zinc oxide morphology was flaky, with an average lateral size of 0.8 μm and a diameter-to-thickness ratio of 50:1.

[0097] The composite material is prepared by mixing and curing 90 parts of polyphenylene ether, 10 parts of heterogeneous structure filler, methyltetrahydrophthalic anhydride and 2-ethylimidazole to obtain the composite material, wherein the mass ratio of methyltetrahydrophthalic acid to polyphenylene ether is 40:100, and the mass ratio of 2-ethylimidazole to polyphenylene ether is 1:100; the curing conditions are pre-curing at 100°C for 1 hour, and then curing at 180°C for 5 hours.

[0098] Embodiment 5:

[0099] A composite material containing a heterogeneous structure filler comprises 65 parts of epoxy resin and 35 parts of a heterogeneous structure filler of zinc oxide-coated zinc copper pyrophosphate.

[0100] The preparation of the heterogeneous structure filler comprises the following steps:

[0101] (1) Raw material mixing: Copper oxide, zinc oxide and phosphoric acid were mixed in a molar ratio of 1.4:0.6:2 to obtain a powder. The powder, agate grinding balls and acetone were then mixed evenly in a mass ratio of 1:9:1, and ball milled at a speed of 200 rpm for 6 h. Finally, the ball milled product was dried to obtain a zinc copper pyrophosphate precursor.

[0102] (2) Precursor calcination: The zinc copper pyrophosphate precursor obtained in step (1) was pre-calcined at a calcination temperature of 800° C. and a calcination time of 1 h, respectively. After the product was cooled to room temperature, it was secondary calcined at a calcination temperature of 900° C. and a calcination time of 4 h, respectively. After cooling, the calcined product was ground according to step (1) to obtain a negative thermal expansion filler zinc copper pyrophosphate powder having an average particle size of 5 μm.

[0103] (3) Seed formation: zinc sulfate and sodium hydroxide are dissolved in an ethanol solvent at a mass ratio of 2:1, and then the zinc copper pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc sulfate is 1:0.01), and the mixture is fully mixed. After separation, washing, and drying, zinc copper pyrophosphate supported by zinc oxide seeds is obtained, which is recorded as Zn 0.6 Cu 1.4 P 2 O 7 @ZnO-dot.

[0104] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 2:1, wherein the concentration of zinc nitrate hexahydrate was 0.03 mol / L, and the Zn obtained in step (3) was added thereto. 0.6 Cu 1.4 P 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and Zn 0.6 Cu 1.4 P 2 O 7 The mixture was stirred at 85°C for 3 h, filtered under reduced pressure, washed, and dried in vacuo at 60°C to obtain a zinc oxide-coated zinc copper pyrophosphate heterostructure filler, wherein the zinc oxide morphology was spherical and its average diameter was 0.5 μm.

[0105] The composite material is prepared by mixing and curing 65 parts of epoxy resin, 35 parts of heterogeneous structure filler and isophorone diamine to obtain the composite material, wherein the mass ratio of isophorone diamine to epoxy resin is 24:100, and the curing conditions are pre-curing at 80°C for 2 hours and then curing at 120°C for 6 hours.

[0106] Embodiment 6:

[0107] A composite material containing a heterogeneous structure filler comprises 70 parts of polyimide and 30 parts of a heterogeneous structure filler of zinc oxide-coated zinc iron pyrophosphate.

[0108] The preparation of the heterogeneous structure filler comprises the following steps:

[0109] (1) Raw material mixing: ferrous oxide, zinc oxide and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.5:0.5:2 to obtain a powder. The powder, agate grinding balls and isopropanol were then mixed evenly in a mass ratio of 1:6:1, and sand-milled at a speed of 400 rpm for 3 h. Finally, the sand-milled product was dried to obtain a zinc iron pyrophosphate precursor.

[0110] (2) Precursor calcination: The zinc iron pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature and a calcination time of 600° C. and 4 h, respectively; after the product is cooled to room temperature, it is secondary calcined at a calcination temperature and a calcination time of 950° C. and 2 h, respectively; after cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler zinc iron pyrophosphate powder having an average particle size of 0.5 μm.

[0111] (3) Seed formation: zinc chloride and sodium hydroxide are dissolved in a methanol solvent at a mass ratio of 3:1, and then the pyrophosphate iron zinc powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc chloride is 1:0.4), and the mixture is fully mixed. After separation, washing, and drying, the pyrophosphate iron zinc supported by zinc oxide seeds is obtained, which is recorded as Zn 0.5 Fe 1.5 P 2 O 7 @ZnO-dot.

[0112] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 5:1, wherein the concentration of zinc nitrate hexahydrate was 0.04 mol / L, and the Zn obtained in step (3) was added thereto. 0.5 Fe 1.5 P 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and Zn 0.5 Fe 1.5 P 2 O 7 The mixture was stirred at 100°C for 5 hours, and then centrifuged, washed, and dried at 120°C to obtain a zinc oxide-coated zinc iron pyrophosphate heterostructure filler, in which the zinc oxide morphology was needle-like, with a length of 1 μm and an aspect ratio of 2:1.

[0113] The composite material is prepared by mixing and curing 70 parts of polyimide, 30 parts of heterogeneous structure filler and 2-ethylimidazole to obtain the composite material, wherein the mass ratio of 2-ethylimidazole to polyimide is 4:100, and the curing conditions are pre-curing at 60°C for 2 hours and then curing at 170°C for 3 hours.

[0114] Embodiment 7:

[0115] A composite material containing a heterogeneous structure filler comprises 95 parts of polydimethylsiloxane and 5 parts of a heterogeneous structure filler of barium zinc pyrophosphate coated with zinc oxide.

[0116] The preparation of the heterogeneous structure filler comprises the following steps:

[0117] (1) Raw material mixing: barium oxide, zinc oxide and ammonium dihydrogen phosphate were mixed at a molar ratio of 0.5:1.5:2 to obtain a powder. The powder, agate grinding balls and deionized water were then mixed evenly at a mass ratio of 1:5:1, and ball milled at a speed of 500 rpm for 6 hours. Finally, the ball milled product was dried to obtain a barium zinc pyrophosphate precursor.

[0118] (2) Precursor calcination: The barium zinc pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 700° C. and a calcination time of 3 h, respectively; after the product is cooled to room temperature, it is secondary calcined at a calcination temperature of 1000° C. and a calcination time of 1 h, respectively; after cooling, the calcined product is ground according to step (1) to obtain a negative thermal expansion filler barium zinc pyrophosphate powder having an average particle size of 0.1 μm.

[0119] (3) Seed formation: zinc acetate and sodium hydroxide are dissolved in an ethanol solvent at a mass ratio of 1.5:1, and then the barium zinc pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc acetate is 1:1), and the mixture is fully mixed. After separation, washing, and drying, the barium zinc pyrophosphate supported by zinc oxide seeds is obtained, which is denoted as Zn 1.5 Ba 0.5 P 2 O 7 @ZnO-dot.

[0120] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 4:1, wherein the concentration of zinc nitrate hexahydrate was 0.08 mol / L, and the Zn obtained in step (3) was added thereto. 1.5 Ba 0.5 P 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and Zn 1.5 Ba 0.5 P 2 O 7 The mixture was stirred at 90°C for 4 hours, and then gravity filtered, washed, and vacuum dried at 75°C to obtain a heterogeneous structure filler of zinc oxide-coated barium zinc pyrophosphate, in which the zinc oxide morphology was flaky, with an average lateral size of 0.3 μm and a diameter-to-thickness ratio of 25:1.

[0121] The composite material is prepared by mixing and curing 95 parts of polydimethylsiloxane, 5 parts of heterogeneous structure filler and 2-methylimidazole to obtain the composite material, wherein the mass ratio of 2-methylimidazole to polydimethylsiloxane is 5:100, and the curing conditions are pre-curing at 70°C for 2 hours and then curing at 120°C for 5 hours.

[0122] Embodiment 8:

[0123] A composite material containing a heterogeneous structure filler comprises 85 parts of polyphenylene ether and 15 parts of a heterogeneous structure filler of zinc oxide-coated zinc cobalt pyrophosphate.

[0124] The preparation of the heterogeneous structure filler comprises the following steps:

[0125] (1) Raw material mixing: Cobalt oxide, zinc oxide and metaphosphoric acid were mixed at a molar ratio of 0.4:1.6:2 to obtain a powder. The powder, agate grinding balls and ethanol were then mixed evenly at a mass ratio of 1:8:1, and sand-milled at a speed of 350 rpm for 2 h. Finally, the sand-milled product was dried to obtain a zinc cobalt pyrophosphate precursor.

[0126] (2) Precursor calcination: The zinc cobalt pyrophosphate precursor obtained in step (1) was pre-calcined at a calcination temperature of 650° C. and a calcination time of 3 h, respectively; after the product was cooled to room temperature, it was secondary calcined at a calcination temperature of 850° C. and a calcination time of 3 h, respectively; after cooling, the calcined product was ground according to the method of step (1) to obtain a negative thermal expansion filler zinc cobalt pyrophosphate powder having an average particle size of 10 μm.

[0127] (3) Seed formation: zinc acetate dihydrate and sodium hydroxide are dissolved in a methanol solvent at a mass ratio of 2.5:1, and then the zinc cobalt pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc acetate dihydrate is 1:0.06), and the mixture is fully mixed. After separation, washing, and drying, zinc cobalt pyrophosphate supported by zinc oxide seeds is obtained, which is recorded as Zn 1.6 Co 0.4 P 2 O 7 @ZnO-dot.

[0128] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 3:1, wherein the concentration of zinc nitrate hexahydrate was 0.07 mol / L, and the Zn obtained in step (3) was added thereto. 1.6 Co 0.4 P 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and Zn 1.6 Co 0.4 P 2 O 7 The mixture was stirred at 85°C for 6 hours, filtered under reduced pressure, washed, and dried by heating at 150°C to obtain a zinc oxide-coated zinc cobalt pyrophosphate heterostructure filler, in which the zinc oxide morphology was needle-shaped, with a length of 1 μm and an aspect ratio of 5:1.

[0129] The composite material is prepared by mixing and curing 85 parts of polyphenylene ether, 15 parts of heterogeneous structure filler and 2-phenylimidazole to obtain the composite material, wherein the mass ratio of 2-phenylimidazole to polyphenylene ether is 6:100, and the curing conditions are pre-curing at 70°C for 2 hours and then curing at 120°C for 5 hours.

[0130] Embodiment 9:

[0131] A composite material containing a heterogeneous structure filler comprises 90 parts of polydimethylsiloxane and 10 parts of a heterogeneous structure filler of zinc oxide-coated zinc strontium pyrophosphate.

[0132] The preparation of the heterogeneous structure filler comprises the following steps:

[0133] (1) Raw material mixing: Strontium oxide, zinc oxide and pyrophosphate were mixed at a molar ratio of 1.8:0.2:2 to obtain a powder. The powder, agate grinding balls and acetone were then mixed evenly at a mass ratio of 1:9:2, and ball milled at a speed of 200 rpm for 5 h. Finally, the ball milled product was dried to obtain a zinc strontium pyrophosphate precursor.

[0134] (2) Precursor calcination: The strontium zinc pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 800° C. and a calcination time of 4 h, respectively; the product is cooled to room temperature and then subjected to secondary calcination at a calcination temperature of 950° C. and a calcination time of 2 h, respectively; after cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler strontium zinc pyrophosphate powder having an average particle size of 15 μm.

[0135] (3) Seed formation: zinc nitrate hexahydrate and sodium hydroxide are dissolved in an ethanol solvent at a mass ratio of 1:1, and then the zinc strontium pyrophosphate powder obtained in step (2) is added (wherein the mass ratio of the negative thermal expansion filler to zinc nitrate hexahydrate is 1:0.6), and the mixture is fully mixed. After separation, washing, and drying, zinc oxide seed-supported zinc strontium pyrophosphate is obtained, which is recorded as Zn 0.2 Sr 1.8 P 2 O 7 @ZnO-dot.

[0136] (4) Crystal growth: Zinc nitrate hexahydrate and hexamethylenetetramine were dissolved in deionized water at a molar ratio of 1:1, wherein the concentration of zinc nitrate hexahydrate was 0.05 mol / L, and the Zn obtained in step (3) was added thereto. 0.2 Sr 1.8 P 2 O 7 @ZnO-dot(zinc nitrate hexahydrate and Zn 0.2 Sr 1.8 P 2 O 7@ZnO-dot has a mass ratio of 3.5:1), stirred at 100°C for 8 hours, and then centrifuged, washed, and vacuum dried at 75°C to obtain a heterogeneous structure filler of zinc oxide-coated strontium zinc pyrophosphate, in which the zinc oxide morphology is flaky, with an average lateral size of 0.1 μm and a diameter-to-thickness ratio of 20:1.

[0137] The preparation method of the composite material is: 90 parts of polydimethylsiloxane, 10 parts of heterogeneous structure filler, methyl hexahydrophthalic anhydride and 2,4-dimethylimidazole are mixed and cured to obtain the composite material, wherein the mass ratio of methyl hexahydrophthalic anhydride to polydimethylsiloxane is 90:100, and the mass ratio of 2,4-dimethylimidazole to polydimethylsiloxane is 1:100; the curing conditions are pre-curing at 100°C for 2 hours, and then curing at 150°C for 5 hours.

[0138] Comparative Example 1

[0139] Pure epoxy resin material.

[0140] Comparative Example 2

[0141] A composite material containing a negative thermal expansion filler comprises 70 parts of epoxy resin and 30 parts of zinc magnesium pyrophosphate filler.

[0142] The preparation of the zinc magnesium pyrophosphate filler comprises the following steps:

[0143] (1) Raw material mixing: Magnesium oxide, zinc oxide and ammonium dihydrogen phosphate were mixed at a molar ratio of 0.4:1.6:2 to obtain a powder. The powder, agate grinding balls and ethanol were then mixed evenly at a mass ratio of 1:7:2, and ball milled at a speed of 300 rpm for 3 h. Finally, the ball milled product was dried to obtain a zinc magnesium pyrophosphate precursor.

[0144] (2) Precursor calcination: The zinc magnesium pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 800° C. and a calcination time of 2 h, respectively; after the product is cooled to room temperature, it is secondary calcined at a calcination temperature of 900° C. and a calcination time of 2 h, respectively; after cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler zinc magnesium pyrophosphate powder having an average particle size of 2 μm.

[0145] The composite material is prepared by mixing and curing 70 parts of epoxy resin, 30 parts of zinc magnesium pyrophosphate filler, methyl hexahydrophthalic anhydride and 2,4-dimethylimidazole to obtain the composite material, wherein the mass ratio of methyl hexahydrophthalic anhydride to epoxy resin is 95:100, and the mass ratio of 2,4-dimethylimidazole to epoxy resin is 1:100; the curing conditions are pre-curing at 100°C for 2 hours, and then curing at 150°C for 5 hours.

[0146] Comparative Example 3

[0147] A composite material containing a hybrid filler comprises 70 parts of epoxy resin and 30 parts of zinc magnesium pyrophosphate filler and zinc oxide filler (the mass ratio of zinc magnesium pyrophosphate filler to zinc oxide filler is 2.6:1). The zinc oxide is a commercial filler with an average particle size of 500 nm.

[0148] The preparation of the zinc magnesium pyrophosphate filler comprises the following steps:

[0149] (1) Raw material mixing: Magnesium oxide, zinc oxide and ammonium dihydrogen phosphate were mixed at a molar ratio of 0.4:1.6:2 to obtain a powder. The powder, agate grinding balls and ethanol were then mixed evenly at a mass ratio of 1:7:2, and ball milled at a speed of 300 rpm for 3 h. Finally, the ball milled product was dried to obtain a zinc magnesium pyrophosphate precursor.

[0150] (2) Precursor calcination: The zinc magnesium pyrophosphate precursor obtained in step (1) is pre-calcined at a calcination temperature of 800° C. and a calcination time of 2 h, respectively; after the product is cooled to room temperature, it is secondary calcined at a calcination temperature of 900° C. and a calcination time of 2 h, respectively; after cooling, the calcined product is ground according to the method of step (1) to obtain a negative thermal expansion filler zinc magnesium pyrophosphate powder having an average particle size of 2 μm.

[0151] The composite material is prepared by mixing and curing 70 parts of epoxy resin, 30 parts of zinc magnesium pyrophosphate filler and zinc oxide filler, methyl hexahydrophthalic anhydride and 2,4-dimethylimidazole to obtain the composite material, wherein the mass ratio of methyl hexahydrophthalic anhydride to epoxy resin is 95:100, and the mass ratio of 2,4-dimethylimidazole to epoxy resin is 1:100; the curing conditions are pre-curing at 100°C for 2 hours, and then curing at 150°C for 5 hours.

[0152] Figure 1 This is a scanning electron microscope photo of zinc oxide-coated magnesium zinc pyrophosphate in Example 1. Figure 2 This is a scanning electron microscope photo of magnesium zinc pyrophosphate that is not coated with a material in Comparative Example 2. From the figure, it can be seen that the flaky zinc oxide is evenly coated on the surface of magnesium zinc pyrophosphate.

[0153] Figure 3 and Figure 4 The thermal conductivity and thermal expansion performance diagrams of the composite materials of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 are shown respectively. When the filler filling amount is 30 vol%, compared with Comparative Example 1 and Comparative Example 2, the composite material of Example 1 exhibits higher thermal conductivity and lower thermal expansion coefficient, which is due to the heterogeneous structure filler in which the thermal conductive filler encapsulates the negative thermal expansion filler in the polymer matrix, which effectively improves the comprehensive performance of the composite material. The material of the present invention has a high application prospect in the field of electronic packaging materials.

[0154] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite material, characterized in that: It includes 65 to 95 parts by volume of a polymer matrix and 5 to 35 parts by volume of a heterogeneous structure filler; Wherein, the heterogeneous structure filler includes a negative thermal expansion filler and a thermal conductive filler, and the thermal conductive filler is coated on the outer layer of the negative thermal expansion filler.

2. The composite material according to claim 1, characterized in that The polymer matrix is ​​at least one of epoxy resin, polyimide, phenolic resin, polyphenylene ether and polydimethylsiloxane. Preferably, the negative thermal expansion filler is zinc pyrophosphate, denoted as Zn 2-x M x P2O7, wherein M is selected from any one of Cu, Mg, Ca, Mn, Fe, Co, Ni, Ba, Sr, and 0<x<2. Preferably, the average particle size of the negative thermal expansion filler is 0.1-30 μm.

3. The composite material according to claim 1, characterized in that The thermal conductivity of the thermally conductive filler is 60-70 W / m·K. Preferably, the thermally conductive filler is zinc oxide.

4. The method for preparing the composite material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (S1) preparing or preparing a negative thermal expansion filler; (S2) coating the outer layer of the negative thermal expansion filler with a thermally conductive filler to obtain a heterogeneous structure filler; (S3) Mixing and curing the heterogeneous structure filler, polymer matrix and curing agent to obtain the composite material.

5. The method according to claim 4, characterized in that In step (S1), the preparation method of the negative thermal expansion filler is as follows: (1) Raw material mixing: mixing an oxide containing an M element, zinc oxide and a phosphorus oxyacid compound, and grinding the obtained mixed powder to obtain a zinc pyrophosphate precursor; The M is selected from any one of Cu, Mg, Ca, Mn, Fe, Co, Ni, Ba, and Sr; (2) Precursor calcination: calcining the zinc pyrophosphate precursor obtained in step (1), grinding the calcined product to obtain a negative thermal expansion filler. Preferably, in step (S2), the preparation method of the heterogeneous structure filler is specifically: (3) Seed formation: Dissolve the soluble zinc salt in an alcohol solvent of sodium hydroxide, then add the negative thermal expansion filler of step (2) and mix to obtain zinc pyrophosphate supported by zinc oxide seeds, denoted as Zn 2-x M x P2O7@ZnO-dot; (4) Crystal growth: Zinc nitrate hexahydrate, hexamethylenetetramine and the Zn obtained in step (3) are added to the mixture. 2-x M x The P2O7@ZnO-dot is heated and mixed in water to obtain the heterogeneous structure filler.

6. The method according to claim 5, characterized in that In step (1), the phosphorus oxyacid compound is one or more of diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, metaphosphoric acid, and pyrophosphoric acid. Preferably, the oxide containing the M element is selected from one of magnesium oxide, calcium oxide, manganese oxide, ferrous oxide, cobalt oxide, nickel oxide, barium oxide or strontium oxide. Preferably, in step (2), the calcination atmosphere is air. Preferably, in step (2), the calcination is specifically: pre-calcination is first performed, the pre-calcined product is cooled, and then secondary calcination is performed; The pre-calcination temperature is 600-800°C, and the pre-calcination time is 1-4h; The secondary calcination temperature is 800-1000°C, and the secondary calcination time is 1-4h.

7. The method according to claim 5, characterized in that In step (3), the soluble zinc salt is at least one of zinc acetate, zinc acetate dihydrate, zinc nitrate hexahydrate, zinc chloride, and zinc sulfate. Preferably, in step (3), the mass ratio of the soluble zinc salt to sodium hydroxide is (0.7-4):

1. Preferably, in step (3), the mass ratio of the negative thermal expansion filler to the soluble zinc salt is 1:(0.01-1).

8. The method according to claim 5, characterized in that In step (4), the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is (0.5-5):

1. Preferably, in step (4), zinc nitrate hexahydrate and Zn 2-x M x The mass ratio of P2O7@ZnO-dot is 1:(0.2~4). Preferably, in step (4), the heating temperature is 80 to 100° C. and the mixing time is 3 to 9 hours.

9. The method according to claim 4, characterized in that In step (S3), the curing agent is at least one of 2-methylimidazole, 2,4-dimethylimidazole, 2-ethylimidazole, 2-phenylimidazole, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, triethylenetetramine, and isophoronediamine. Preferably, in step (S3), the curing conditions are pre-curing at 50-100°C for 1-3 hours, and then curing at 120-180°C for 3-8 hours. Preferably, in step (S3), the mass ratio of the curing agent to the polymer matrix is ​​(1-96):

100.

10. Use of the composite material according to any one of claims 1 to 3 in electronic packaging materials or thermal interface materials.

Citation Information

Patent Citations

  • Negative thermal expansion composite material and preparation method thereof

    CN103450844A

  • Low-temperature seal glass material and preparation method of composite filler

    CN104496183A

  • Low-thermal-expansion-coefficient insulating adhesive film and preparation method thereof

    CN112662334A

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN113903918A

  • Negative thermal expandable glass ceramic and method for producing the same

    JP2001172048A